Shaping the Dawn of Islam in Germany (1983-1989): Al-Fadschr, the Twelver Shiite Magazine of the Islamic Center Hamburg - Gümmer, Johann Christoph (Oriente moderno, 2025)
Al-Fadschr, published by the Islamic Center Hamburg in 1983-2018, was the first German-language Twelver Shiite Periodical. Using a "system-oriented approach" and Birgit Meyer’s concept of "aesthetic formations", the study analyzes its early phase (1983-1989), highlighting the magazine’s role within the emerging Muslim public sphere and its significance for pan-Islamic community formation in Germany in the specific context of the early Islamic, multi-confessional umbrella organization Treffen deutschsprachiger Muslime ("Gathering of German speaking Muslims", TDM).